A simple procedure for detecting Dekkera bruxellensis in wine environment by RNA-FISH using a novel probe - Branco, P (2021)
Dekkera bruxellensis, considered the major microbial contaminant in wine production, produces 4-ethylphenol, a cause of unpleasant odors. Thus, identification of this yeast before wine spoilage is crucial. Although challenging, it could be achieved using a simple technique: RNA-FISH. To reach it is necessary to design probes that allow specific detection/identification of D. bruxellensis among the wine microorganisms and in the wine environment and, if possible, using low formamide concentrations. Therefore, this study was focused on: a) designing a DNA-FISH probe to identify D. bruxellensis that matches these requirements and b) determining the applicability of the RNA-FISH procedure after the end of the alcoholic fermentation and in wine. A novel DNA-FISH D. bruxellensis probe with good performance and specificity was designed. The application of this probe using an in-suspension RNA-FISH protocol (applying only 5% of formamide) allowed the early detection/identification of D. bruxellensis at low cell densities (5×102 cell/mL). This was possible by flow cytometry independently of the growth stage of the target cells, both at the end of the alcoholic fermentation and in wine even in the presence of high S. cerevisiae cell densities. Thus, this study aims to contribute to facilitate the identification of D. bruxellensis before wine spoilage occurs, preventing economic losses to the wine industry.